Avaliação micológica de pernis maturados ovinos e do ar ambiente ao longo do processamento - Almeida, Tiago Santos de (2022)
The elaboration of cured and matured meat products, specifically legs, is traditional in several European countries. In the Rio Grande do Sul, the presence of Italian and German descendants may have helped in the development of these products, contributing to the elaboration of sheep meat products in the state. In search of adding value and aiming to provide sensory characteristics to the product, fungal species present on the surface and in the ambient air of the process and associated with the maturation stage can influence the quality and contribute to the formation of the aromatic profile. Thus, the objective of this work was the characterization of the fungal species present on the surfaces of the legs over the 180 days, as well as the presence of spores in the ambient air of the processing areas. Thus, aged hams were experimentally prepared from lamb hams, with the development of two treatments: (T1) without the addition of seasonings and spices and (T2) with the addition of black and white pepper, nutmeg, garlic, marjoram, and onion. After salting, the legs went through the stages of drying, smoking, and maturation in an acclimatized chamber for 180 days. Analyzes were carried out in the raw material and other ingredients, and in the air of the processing areas before the elaboration of the hams. During maturation, samples were taken on days 0, 45, 90, and 180 in the legs and the air. For the hams, the surface swab technique was used and for the air, an air sampler was used. The samples were incubated for 7 days at 25 °C and the fungal colonies were isolated and identified. In the initial stage of maturation, no fungi were identified in the sheep legs (detection limit = 100 CFU/cm2). After 45 days of maturation, a greater similarity of the fungal species present in the sheep legs of the T1 treatment with those occurring in ambient air was observed, while in the T2 they showed a greater relationship with the species present in the condiments/spices. During maturation, the fungi present in the air of the maturation chamber began to be influenced by the species installed in the T2 hams and to influence the non-spiced ones (T1). At the end of maturation, the total fungal count was 5.78 log CFU/cm2 for T1 and 7.19 log CFU/cm2 for T2 legs; in addition to the mycobiota exclusively composed of xerophilic species of Aspergillus section Aspergillus, for T2. In ambient air, the predominance of the genus Cladosporium sp. The potentially ochratoxigenic species Aspergillus westerdijkiae was detected at the end of maturation only in T1 hams. Thus, the seasoning influenced the fungal species that established themselves on the surfaces of the products throughout the maturation stage, with great relevance to the fungi occurring in the ambient air. From these results, it is concluded that the presence of fungi on the surfaces of sheep legs helps to protect against toxigenic and pathogenic fungal species, without.